Better Together: Conditions for Implementing Innovations to Improve Quality of Care in Health Delivery Organizations - Kievit, Pieter; Bons, Roger W.H.; Roijakkers, Nadine (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
The necessary resilience of healthcare delivery organizations to cope with a changing and ever challenging socio-economic environment depends on continuous, effective innovation, based on the adoption of proven interventions. It is aimed at increasing output quality of care, thus better responding to demands of patients, staff and stakeholders. Although expectations of (digital) innovation in healthcare are generally high, the outcomes often do not meet these expectations. In a scoping review of 46 research papers on innovation, we analyzed which factors were reported as barriers and facilitators for success or failure of innovation initiatives. The mayority of papers reported a variety of conditions and a limited use of available implementation frameworks. Furthermore, the underlying model of quality of care was often incomplete, thereby compromising the outcome of the initiative, hampering effective dissemination and implementation of interventions and the means for valid outcome research of innovation projects.